2022
DOI: 10.3390/electronics11020283
|View full text |Cite
|
Sign up to set email alerts
|

Fog-Computing-Based Cyber–Physical System for Secure Food Traceability through the Twofish Algorithm

Abstract: The Internet is an essential part of daily life with the expansion of businesses for maximizing profits. This technology has intensely altered the traditional shopping style in online shopping. Convenience, quick price comparison, saving traveling time, and avoiding crowds are the reasons behind the abrupt adoption of online shopping. However, in many situations, the product provided does not meet the quality, which is the primary concern of every customer. To ensure quality product provision, the whole food s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…In this section, we study the security framework in CPS cloud and compare the performance of our suggested technique to that of other existing methods. The existing methods are RSA [22], Twofish algorithm [23], improved chacha20 algorithm (ICC [24]), Fully Homomorphic encryption algorithm (FHEA [25]). Encryption time analyses and illustrates the average amount of time required to encrypt media content files as input.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, we study the security framework in CPS cloud and compare the performance of our suggested technique to that of other existing methods. The existing methods are RSA [22], Twofish algorithm [23], improved chacha20 algorithm (ICC [24]), Fully Homomorphic encryption algorithm (FHEA [25]). Encryption time analyses and illustrates the average amount of time required to encrypt media content files as input.…”
Section: Resultsmentioning
confidence: 99%
“…Larger encrypted data makes two fish safe. This big size may slow down the application if it's applied to significant amounts of unencrypted data [23]. Slower encryption speed as encryption and decryption both require capturing the complete block.…”
Section: Discussionmentioning
confidence: 99%
“…The most common form of key whitening is the XOREncrypt XOR method. It uses a simple XOR operation before the first round of encryption and after the last round of encryption ( Awan et al, 2022 ).…”
Section: Iot Security Solutionsmentioning
confidence: 99%